Analysis of Demand and Economic Value of Sambolo Beach Tourism, Serang Regency, Banten - Eka Rizky Pratiwi; Erlinda Indrayani (Faculty of Fisheries and Marine Science, Brawijaya University, 2019)
This research was already implemented in Sambolo Beach Tourism, Serang, Banten. The purpose of this study is to investigate and analyze: (1) characteristics of travelers and characteristics of Sambolo Beach, (2) factor or independet variables (cost of trip, age, education level, distance, income, working time, facilities and experience) significantly affect to request Sambolo visitors to the beach, (3) and the economic value of Sambolo Beach as a tourism. The sampling was taken by quoted accidental sampling method of 36 respondents. Data were collected by observation, documentation, interview, and questionnare. Analyzing data were done by multiple regression analysis method and Individual Travel Cost Method. Data analysis done by using SPSS for Windows 16.The results showed that all the independent variables jointly affect the number of visitor’s demand to the Sambolo Beach, while variables that effect to the number of visitors to the Sambolo Beach were only 4 variables, the variables cost of trip, income, facillities, and experience. Consumer surplus value of IDR 430.232 per individual per one visit, so that the economic value of Sambolo Beach is IDR 36.279.969.600 per year in 2015 (the result of multiplying the consumer surplus and the number of visitors in 2015). Developing of Sambolo Beach, through improvement in all aspects are important to do.